ANALISIS KINEMATIK DAN DINAMIK MEKANISME PENGGERAK 2-DOF UNTUK ANTENA BERGERAK PADA KOMUNIKASI SATELIT - Saputra, Hendri Maja; Rijanto, Estiko (LIPI Press, 2009)
Kinematic and dynamic analysis of a mechanism for mobile antennas used in positioning control system of mobile satellite communication (SATCOM) antennas has been conducted. This antenna driving mechanism has two degrees of freedom (2-DOF), they are azimuth and elevation directions. The antenna driving mechanism is put on a vehicle (either land or water), so that the analysis includes vehicle body disturbance in three directions (3-DOF), namely roll, pitch, and yaw. The dynamical model has been made using D-H notation which is common in robotics. Computer simulation has been conducted to analyze the relationship between the antenna movement velocity (azimuth and elevation direction) and the required actuator torque to control the mechanism so that the antenna always keeps pointing to a satellite 630 km above the earth surface. The simulation results show that antenna movement needs smaller actuator torque in smaller elevation and larger actuator torque in larger elevation. For the antenna dimension and the antenna driving mechanism used in this research, it is obtained that nominal value of actuator torque for pan (azimuth) direction is 30 Nm and for tilt (elevation) direction is 200 Nm.